Self-assessment of Entrepreneurship Competency Level Among Students in The Technical Field at Kuala Lumpur Malaysian Spanish Institute University - Azizan, Norazra; Othman, Hasyamuddin (Research and Innovation in Technical and Vocational Education and Training, 2024)
This research highlights the importance of entrepreneurship in reducing poverty and supporting the economic growth of the country. In this context, graduates with low entrepreneurial competence are considered vulnerable in the job market. Therefore, this study aims to identify the self-assessment of the level of entrepreneurial competence among students at the University Kuala Lumpur Malaysian Spanish Institute. The research methodology involves survey research with a quantitative approach, using a Google form questionnaire. Research instruments were used from Management Systems International (MSI) and Mcber to assess entrepreneurial competence. The study respondents consisted of 144 undergraduate students at UniKL MSI. Descriptive statistical analysis was used to evaluate the mean value of the PEC score, and T-test to test the differences between gender and students who have currently and already taken the entrepreneurship course. The findings of the study show that the level of entrepreneurial competence, especially in setting goals, is high among students. In addition, self-confidence shows that there is a significant difference between students who currently are taking entrepreneurship courses and students who have taken entrepreneurship courses. Next, the commitment to the work contract shows that there is a significant difference between men and women. In conclusion, this study provides insights to help students develop their entrepreneurial competencies. The implications of this research can, to some extent, contribute to raising awareness of entrepreneurship from the perspective of students' self-assessed entrepreneurial competencies.